Adenoids in children: Advances in immunology, diagnosis, and surgery. Issue 3 (18th February 2014) - Brambilla, Ilaria; Pusateri, Alessandro; Pagella, Fabio; Caimmi, Davide; Caimmi, Silvia; Licari, Amelia; Barberi, Salvatore; Castellazzi, Annamaria M.; Marseglia, Gian Luigi
<x xml:space="preserve">Abstract</x> Adenoids are strategically located for mediating local and regional immune functions as they are exposed to antigens from both the outside air and the alimentary tract. Recurrent or chronic respiratory infections can induce histomorphological and functional changes in the adenoidal immunological barrier, sometimes making surgical treatment necessary. Our aim in this review is to summarize the crucial points about not only the immunological histopathology of adenoidal tissue, especially in patients with adenoid hypertrophy, but also the most common and useful diagnostic techniques and surgical options. Clin. Anat. 27:346–352, 2014. © 2014 Wiley Periodicals, Inc.